2018
DOI: 10.1111/ecpo.12110
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous trade policy in general equilibrium: An interaction of redistribution rule, trade openness, and labor market condition

Abstract: Using a general equilibrium framework, the paper derives trade policy endogenously for a small country. It shows that, contrary to the existing literature, a lobbying industry is not guaranteed trade protection; it may even face trade taxes. Besides lobbying, trade policy depends on other factors such as the trade revenue distribution rule, income distribution across groups, trade openness, factor substitutability in production, industry employment size, and labor market flexibility. The paper also shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Likewise, Soderbery (2018) argued that the optimal tariffs vary in accordance to heterogeneous supply elasticities. Acharya (2018) revealed that lobbying has significant effects on trade policy, resulting in government preference for import tariffs over export subsidies. Moreover, Akcigit et al (2018) provided some empirical evidence of the potential welfare losses generated from tariffs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, Soderbery (2018) argued that the optimal tariffs vary in accordance to heterogeneous supply elasticities. Acharya (2018) revealed that lobbying has significant effects on trade policy, resulting in government preference for import tariffs over export subsidies. Moreover, Akcigit et al (2018) provided some empirical evidence of the potential welfare losses generated from tariffs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Essentially, each country decides its own trade policy -are they open to trade with other countries, if so, what is the level of openness, is there any sectors that will be protected, are there any countries included into non-tradable partners list and so on. Usually trade policies aimed to the direction (Acharya, 2018) of two main externalities (or somewhere in between) such as trade liberalization or trade protection (Ito, Mukunoki, Tomiura, & Wakasugi, 2019) or sometimes called as free trade and protectionism (Acharya, 2018; Saha, 2019) which is measured by country's trade openness (Acharya, 2018). Commonly, any government interventionist policy that is trying to influence country's trade (except new trade agreements) is attributed to protectionism.…”
Section: Literature Review On Trade Policies Tariffs and Tariff Evaluationmentioning
confidence: 99%